A first WHO reference reagent for the detection of anti‐human platelet antigen‐15b. Issue 2 (23rd June 2021) - Sharp, Giles; Poles, Anthony; Studholme, Lucy
Abstract: Background and Objectives: Alloantibodies to human platelet antigen‐15b (anti‐HPA‐15b) have been detected in mothers with foetal–neonatal alloimmune thrombocytopenia and in multiply transfused patients. Assays used to detect this antibody, which aids in disease diagnosis, can be unreliable and vary in sensitivity. The objective was to generate a stable, lyophilized anti‐HPA‐15b preparation and evaluate its suitability as a World Health Organization (WHO) reference reagent for use in the quality control of platelet alloantibody detection assays. Results from an international collaborative study to evaluate the preparation were used to assign a minimum potency at which laboratories can be expected to detect the antibody. Materials and Methods: Recalcified plasma containing anti‐HPA‐15b was aliquotted, lyophilized and coded 18/220. Twenty‐five laboratories in 16 countries tested doubling dilutions of the reconstituted material in glycoprotein‐specific assays such as the monoclonal antibody–specific immobilization of platelet antigen assay and reported the last positive (or endpoint) dilution. Results: Twenty‐four laboratories (96%) detected antibodies with HPA‐15b specificity in preparation 18/220. Reported endpoint dilutions were normally distributed with a modal dilution of 1 in 16 and ranged from 1 in 2 to 1 in 128. Only two laboratories (8%) failed to detect anti‐HPA‐15b at 1 in 8 dilution. Conclusions: When diluted 1 in 8, most laboratories detected anti‐HPA‐15b in preparation 18/220 using HPA‐15bb platelets but not with HPA‐15aa platelets. The participants agreed this to be an appropriate dilution for assignment as the minimum potency. In October 2020, the WHO Expert Committee on Biological Standardization approved 18/220 as an International Reference Reagent.